2004
DOI: 10.1246/bcsj.77.785
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-Azaazulenes from Cycloheptatrienylmethyl Ketone O-Pentafluorobenzoyloximes by Palladium-Catalyzed Cyclization and Oxidation

Abstract: Various 1-azaazulenes are synthesized from cycloheptatrienylmethyl ketone O-pentafluorobenzoyloximes by treatment with a catalytic amount of Pd(dba)2–t-Bu3P (dba = dibenzylideneacetone) and triethylamine in the presence of MS 4A via alkylideneaminopalladium(II) intermediates generated by oxidative addition of the oximes to a Pd(0) complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The Pd-catalyzed cyclization of oxime esters with pendant alkenes was first developed by Narasaka and co-workers, providing a direct method for the synthesis of substituted pyrroles (Scheme a) . Following this seminal work, the access to other heterocyclic/aromatic species with other types of oxime esters was further achieved . Recently, Bower reported the cyclization of γ,δ -unsaturated oxime esters via an oxidative addition or a radical process for the construction of C­(sp 3 )–N bonds, significantly extending the Narasaka–Heck reaction to the formation of stereogenic heterocycles (Scheme a). , …”
mentioning
confidence: 99%
“…The Pd-catalyzed cyclization of oxime esters with pendant alkenes was first developed by Narasaka and co-workers, providing a direct method for the synthesis of substituted pyrroles (Scheme a) . Following this seminal work, the access to other heterocyclic/aromatic species with other types of oxime esters was further achieved . Recently, Bower reported the cyclization of γ,δ -unsaturated oxime esters via an oxidative addition or a radical process for the construction of C­(sp 3 )–N bonds, significantly extending the Narasaka–Heck reaction to the formation of stereogenic heterocycles (Scheme a). , …”
mentioning
confidence: 99%
“…Finally, an unprecedented synthetic approach to a variety of 1-azaazulenes was developed by incorporating the c,d-unsaturated moiety in the form of a cycloheptatrienyl group. 27 Good yields for the amino-Heck cyclisation were obtained by using 10 mol% Pd(dba) 2 and 40 mol% P(t-Bu) 3 in the presence of molecular sieves. Successive oxidation of the crude product mixture with MnO 2 yielded the desired product (Scheme 9, eqn ( 18)).…”
Section: Aminopalladation In Aza-heck-type Reactionsmentioning
confidence: 99%
“…Importantly, the oxime ester substrates are readily accessible and further derivatization of the cyclization products is possible by manipulation of either the imine or alkene functionalities.The Pd-catalyzed cyclization of oxime esters with alkenes was first reported by Narasaka, et al and provides an entry to pyrroles via the catalytic generation and trapping of an imino-Pd II intermediate (Scheme 1 b). [3] Applications of the "Narasaka-Heck" method to other heteroaromatic classes [4] and cascade reactions [5] have been reported and the scope of the oxime activating group has been examined. [6] The catalytic generation and trapping of metalated imines has also been exploited in other contexts.…”
mentioning
confidence: 99%
“…[7][8][9] In general, methods that are reliant upon this process produce C(sp 2 )ÀN bonds and are therefore not applicable to the synthesis of chiral N-heterocycles. [3][4][5] Extension to the formation of C(sp 3 ) À N bonds is an attractive possibility but, cascade processes aside, [5a,b] general methods that achieve this have not been reported. Of particular relevance to this study is a single example by Fürstner, et al, who showed that cyclization of oxime ester 1 provided 2 in 54 % yield.…”
mentioning
confidence: 99%